Africa Is Not A Country by Dipo Faloyin. (2nd January 2023) - Robinson, Hina
ABSTRACT: This review of Africa Is Not A Country, the book that has been written to break stereotypes of modern Africa, looks at the importance of narrative and suggests how geography teachers can use the content of Dipo Faloyin's book to develop their own subject knowledge and enhance their teaching about the continent of Africa.